Resveratrol Attenuates Formaldehyde Induced Hyperphosphorylation of Tau Protein and Cytotoxicity in N2a Cells - He, Xiaping; Li, Zhenhui; Rizak, Joshua D.; Wu, Shihao; Wang, Zhengbo; He, Rongqiao; Su, Min; Qin, Dongdong; Wang, Jingkun; Hu, Xintian (Frontiers in Neuroscience, 2017)
Recent studies have demonstrated that formaldehyde (FA) - induced neurotoxicity is important in the pathogenesis of Alzheimer’s disease (AD). Elevated levels of FA have been associated with memory impairments and the main hallmarks of AD pathology, including β-amyloid plaques, tau protein hyperphosphorylation and neuronal loss. Resveratrol (Res), as a polyphenol anti-oxidant, has been considered to have therapeutic potential for the treatment of AD. However, it has not been elucidated whether Res can exert its neuroprotective effects against FA-induced neuronal damages related to AD pathology. To answer this question, the effects of Res were investigated on Neuro-2a (N2a) cells prior to and after FA exposure. The experiments found that pretreatment with Res significantly decreased FA-induced cytotoxicity, reduced cell apoptosis rates and inhibited the hyperphosphorylation of tau protein at Thr181 in a dose-dependent manner. Further tests revealed that this effect was associated with the suppression of glycogen synthase kinase (GSK-3β) and calmodulin-dependent protein kinase II (CaMKII) activities, both of which are important kinases for tau protein hyperphosphorylation. In addition, Res was found to increase the activity of phosphoseryl/phosphothreonyl protein phosphatase-2A (PP2A). In summary, these findings provide evidence that Res protects N2a cells from FA-induced damages and suggests that inhibition of GSK-3β and CaMKII and the activation of PP2A by Res protect against the hyperphosphorylation and/or mediates the dephosphorylation of tau protein respectively. These possible mechanisms underlying the neuroprotective effects of Res against FA-induced damages provide another perspective on AD treatment via inhibition of tau protein hyperhosphorylation.